Quality parameters of water stored in cisterns made of cementitious materials - L. S. Batista; A. C. G. da Silva; A. G. de Oliveira; L. A. Gachet; F. B. Canteras; R. C. C. Lintz (Cerâmica)
Abstract The use of cisterns for water storage has been an alternative to supply water in regions with low rainfall, such as the Brazilian semi-arid region. Several studies have been conducted, proposing the use of different materials for the construction of cisterns. This research analyzed some quality parameters of water stored in cisterns. Two prototype cisterns were built, one with conventional mortar and the other composed of mortar with tire rubber residues, expanded vermiculite, and sisal fibers. The evaluated water quality parameters were: pH, alkalinity, conductivity, turbidity, true color, and apparent color at ages of 24 hours, 7 days, 30 days, 60 days, and 90 days. The results were compared to those obtained from a plastic bench cistern and indicated an increase in pH, alkalinity, and conductivity, which indicates and confirms the formation of salts caused by the cementitious material.